Understanding the factor structure of the public stigma of substance use disorder. (4th March 2019) - Nieweglowski, Katherine; Dubke, Rachel; Mulfinger, Nadine; Sheehan, Lindsay; Corrigan, Patrick W.
Abstract: Few empirical research studies have examined the public stigma of substance use disorder (SUD) compared to mental illness (MI). Expanding on the results of a qualitative study on the stigma of SUD, this study quantitatively examined items thought to represent the three constructs of public stigma: stereotypes, prejudice and discrimination. Additionally, exploratory factor analyses generated factor structures to provide meaning to each construct. Results indicated that some factors were endorsed significantly higher than others: for stereotypes, recklessness and threat were significantly endorsed more than unreliability and inadequacy; for prejudice, dread was endorsed the most; and for discrimination, restriction was endorsed more than invalidation. Additional oneway ANOVAs revealed that women significantly endorsed restriction more than men. Although further research is needed to confirm a complete set of factors, these results may help to establish a model for the public stigma of people with SUD.